2017
DOI: 10.5935/abc.20170052
|View full text |Cite
|
Sign up to set email alerts
|

SAMe-TT2R2 Score in the Outpatient Anticoagulation Clinic to Predict Time in Therapeutic Range and Adverse Events

Abstract: BackgroundThe SAMe-TT2R2 score was developed to predict which patients on oral anticoagulation with vitamin K antagonists (VKAs) will reach an adequate time in therapeutic range (TTR) (> 65%-70%). Studies have reported a relationship between this score and the occurrence of adverse events.ObjectiveTo describe the TTR according to the score, in addition to relating the score obtained with the occurrence of adverse events in patients with nonvalvular atrial fibrillation (AF) on oral anticoagulation with VKAs.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 26 publications
1
11
0
9
Order By: Relevance
“…However, SAMe-TT 2 R 2 overall score was associated with TTR and was the only predictor of poor quality of anticoagulation in the multivariate analysis but only when a score of one was used as a cut-off instead of two. Since SAMe-TT 2 R 2 score was proposed and validated by Apostolakis and colleagues [30], external validation studies in populations from various countries took place and results were mostly positive [35][36][37][38][39][40]. Additionally, the score was tested in deep venous thrombosis as opposed to non-valvular atrial fibrillation patients and it was also shown to have a modest predictive ability for the quality of INR control [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…However, SAMe-TT 2 R 2 overall score was associated with TTR and was the only predictor of poor quality of anticoagulation in the multivariate analysis but only when a score of one was used as a cut-off instead of two. Since SAMe-TT 2 R 2 score was proposed and validated by Apostolakis and colleagues [30], external validation studies in populations from various countries took place and results were mostly positive [35][36][37][38][39][40]. Additionally, the score was tested in deep venous thrombosis as opposed to non-valvular atrial fibrillation patients and it was also shown to have a modest predictive ability for the quality of INR control [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Несмотря на наличие в арсенале врача прямых пероральных антикоагулянтов, варфарин продолжает оставаться широко назначаемым антикоагулянтом [11,12,[31][32][33] При этом данные исследований (как клинических рандомизированных, так и наблюдательных) свидетельствуют о том, что вне целевого уровня антикоагуляции находится не менее 40% пациентов [5][6][7][8][9][10][11][12][13][14]. Наблюдение за больными, получающими варфарин, в условиях созданной в НМИЦ кардиологии патронажной системы свидетельствует о том, что число пациентов со значением TTR <70% составляет 41,6%.…”
Section: Discussionunclassified
“…В нашем исследовании обращает на себя внимание тот факт, что при проведении ROC-анализа как для значения TTR <70%, так и для развития всех тромботических осложнений диагностически значимым критерием для индекса SAMe-TT 2 R 2 оказалось значение 1 балл, в связи с чем использовать данную шкалу для оценки предполагаемой неадекватной антикоагуляции и прогноза невозможно. С нашими данными совпадают результаты исследований [14,20,24,34,35], продемонстрировавших отсутствие корреляции между индексом SAMe-TT 2 R 2 и определяющими прогноз негативными исходами у больных с ФП. Причиной этого, вероятнее всего, является небольшое число пациентов, имевших более 2 баллов, однако их число было сопоставимо с данными международных исследований, выполненных среди представителей европеоидной расы [16,17,[20][21][22].…”
Section: Discussionunclassified
See 2 more Smart Citations